18S rRNA amplicon sequence data (V1–V3) of the Bronx river estuary, New York - Melissa R. Ingala (Pensoft Publishers, 2021)
Characterising and monitoring biological diversity to foster sustainable ecosystems is highly recommended as urban centres rapidly expand. However, much of New York City’s biodiversity remains undescribed, including in the historically degraded, but recovering Bronx River Estuary. In a pilot study to identify organisms and characterise biodiversity patterns there, 18S rRNA gene amplicons (V1–V3 region), obtained from river sediments and surface waters of Hunts Point Riverside and Soundview Parks, were sequenced. Across 48 environmental samples collected over three seasons in 2015 and 2016, following quality control and contaminant removal, 2,763 Amplicon Sequence Variants (ASVs) were identified from 1,918,463 sequences. Rarefaction analysis showed sufficient sampling depth, and community composition varied over time and by substrate at the study sites over the sampling period. Protists, plants, fungi and animals, including organisms of management concern, such as Eastern oysters (Crassostrea virginica), wildlife pathogens and groups related to Harmful Algal Blooms, were detected. The most common taxa identified in river sediments were annelid worms, nematodes and diatoms. In the water column, the most commonly observed organisms were diatoms, algae of the phylum Cryptophyceae, ciliates and dinoflagellates. The presented dataset demonstrates the reach of 18S rRNA metabarcoding for characterising biodiversity in an urban estuary.